GEOCHEMICAL MODELING OF MIXING SCENARIO BETWEEN POTENTIALLY ACID FORMING (PAF) MATERIAL AND FLY ASH IN LABORATORY SCALE KINETIC TEST - A. P. Silalahi, Herbert
One method that can be applied to prevent the formation of acid mine drainage (AMD) is by mixing rocks that have the potential to neutralize the acid with rocks that are potentially acid forming (PAF). Research on using coal ash as a non-acid forming (NAF) material in mixing scenarios to prevent the formation of AMD has been carried out, both in laboratory scale and field scale kinetic tests. However, the kinetic testing procedure is complex, timeconsuming, and requires operator expertise to obtain consistent results. Hence geochemical modeling is needed, which can be an alternative method that can describe the characteristics of the geochemical reaction as a reference in determining the estimation of the performance of the coal ash mixing system.